2010
DOI: 10.1021/ja910825g
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Resulting in the Reductive Ethynylation of Aldehydes: Dissection of Its Components

Abstract: A mild and efficient two-carbon homologation of aldehydes exploiting multiple modes of KOt-Bu was developed. This process involves a sequential Peterson allenylation/allene-alkyne isomerization/ protodesilylation in a single-flask operation. The differential roles played by the various elements of the process were demonstrated through dissection experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Allene-alkyne isomerization ordinarily requires the use of very strong bases . In contrast to the usual processes, the isomerization of the allene of 6 into the corresponding alkyne is promoted by a weak base as acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Allene-alkyne isomerization ordinarily requires the use of very strong bases . In contrast to the usual processes, the isomerization of the allene of 6 into the corresponding alkyne is promoted by a weak base as acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Danishefsky et al found that bis-trimethylsilylvinyl alcohol 74 could be deprotonated with n-BuLi and then treated with KO t Bu to effect transformation to the corresponding allene 76 (Scheme 19b). [40] Mechanistically, a sequence involving transmetalation, Brook rearrangement and elimination was proposed to account for this result. The majority of silyl allenes in this study were not isolated, but were isomerized directly to the corresponding alkynes.…”
Section: Scheme 18 Challenging Elimination In Peterson Allenylationmentioning
confidence: 99%
“…Afterward, D undergoes migratory insertion to form E , which can be converted into allenyne 6′ via protonation or [5]cumulene 4 through 1,3-elimination. Finally, 6′ undergoes a base-assisted proton transfer (BAPT) 5 c ,14 to give the 1,3-diyne product 6 (see ESI† for details), while 4 undergoes the 1,3-H shift twice to form more stable 1-en-3,5-diyne 2 . As shown in deuterium-labelling experiments, the intramolecular 1,3-H shift is also accompanied by intermolecular BAPT.…”
mentioning
confidence: 99%